Application of different metrics for describing light color quality of white LED - Supronowicz, Robert; Fan, Jiajie; Listowski, Maciej; Watras, Adam; Fryc, Irena (Photonics Letters of Poland, 2021)
Using the example of the UV-excited Ca9KMg(PO4)7:1% Eu2+ phosphor, methods for characterizing the color quality of the light emitted by it at different operating temperatures are described. The effect of adopting two different colorimetric observers established by the International Commission on Illumination (i.e., the CIE 1931 observer with a viewing angle of two degrees and the CIE 2015 observer with a viewing angle of ten degrees) on the position of the chromaticity point of light emitted by phosphor is discussed. It was demonstrated that using the CIE 2015 photometric observer to determine the position of the chromaticity point, the tested phosphor is characterized by smaller changes in the color of emitted light as a function of operating temperature than when using the CIE 1931 observer. Full Text: PDF References R. Pązik et al., "Thermal quenching mechanisms of the Eu3+ luminescence in Ca9Al(PO4)7 obtained by citric route", Materials Research Bulletin, Vol. 48, I.2, 337 (2013). CrossRef I. Fryc, S. W. Brown, Y. Ohno, "A spectrally tunable LED sphere source enables accurate calibration of tristimulus colorimeters", Proc. SPIE Vol. 6158, 125 (2006) CrossRef Y. Ohno, "Practical Use and Calculation of CCT and Duv", LEUKOS, 10:1, 47-55, (2014). CrossRef D. Durmus, "Multi-objective optimization trade-offs for color rendition, energy efficiency, and circadian metrics", Proc. SPIE Vol. 11706, 117061J (2021) CrossRef I. Fryc, D. Czyzewski, " Dokładność pomiarowa spektroradiometrów typu CCD", Przeglad Elektrotechniczny R. 85(11), 276 (2009). DirectLink D. Czyzewski, "Zamienniki LED klasycznych żarówek", Przeglad Elektrotechniczny R. 88(11), 123 (2012). DirectLink J. Kusznier, W. Wojtkowski, "Spectral properties of smart LED lamps", Phot. Lett. Pol., 12(1), 16 (2020). CrossRef P. Hung, J. Y. Tsao, "Maximum White Luminous Efficacy of Radiation Versus Color Rendering Index and Color Temperature: Exact Results and a Useful Analytic Expression", Journ. of Display Techn., 9(6), 405 (2013). CrossRef Y. Asano, MD Fairchild, L. Blondé, "Individual Colorimetric Observer Model", PLOS ONE 11(2) e0145671 (2016). CrossRef Y. Wang, M. Wei, "Preference among light sources with different Duv but similar colour rendition: A pilot study", Lighting Res. & Tech., 50(7), 1013 (2018). CrossRef K. A. G. Smet, "Tutorial: The LuxPy Python Toolbox for Lighting and Color Science", LEUKOS, 16:3, 179 (2020). CrossRef D. Petrisor, C. D. Galatanu, C. Haba, L. Breniuc "Color Quality Measurements of LED Light Sources Using Image Processing", EEEIC/I&CPS Europe, 1, (2019) CrossRef ANSI C78.377:2017 DirectLink I. Fryc, T. Dimitrova-Grekow, "An Automated System for Evaluation of the Quality of Light Sources", 2016 IEEE (Lumen V4), 1 (2016). CrossRef Y. Ohno, "Spectral design considerations for white LED color rendering", Optical Engineering 44(11), 111302 (2005). CrossRef E. Purwanto, P. Dupuis, L. Canale, N. I. Sinisuka, G. Zissis, "Aging study of remote luminophore at ambient temperature", EEEIC/I&CPS Europe, 1 (2019). CrossRef J. Fan, Y. Li, I. Fryc, C. Qian, X. Fan, G. Zhang, "Machine-Learning Assisted Prediction of Spectral Power Distribution for Full-Spectrum White Light-Emitting Diode", IEEE Photonics Journal, 12(1), 1 (2020). CrossRef D. Mozyrska, M. Wyrwas, I. Fryc, "Wyznaczanie parametrów kolorymetrycznych LEDa w pełnym zakresie temperatur pracy", Przeglad Elektrotechniczny R. 93(4a), 232 (2012). CrossRef I. Fryc, "Analiza właściwości spektralnych LEDów z zależności od temperatury i natężenia ich prądu pracy", Przeglad Elektrotechniczny R. 86(10), 187 (2010). DirectLink I. Fryc, "Pomiary wybranych parametrów świetlno-optycznych LEDów według zaleceń Międzynarodowej Komisji Oświetleniowej CIE 127:2007", Przeglad Elektrotechniczny R. 85(11), 317 (2009). DirectLink A. David et al., "Development of the IES method for evaluating the color rendition of light sources", Opt. Express 23, 15888 (2015). CrossRef S Jost-Boissard, P Avouac, M Fontoynont, "Assessing the colour quality of LED sources: Naturalness, attractiveness, colourfulness and colour difference", Lighting Research & Technology, 47(7): 769 (2015). CrossRef J. Kowalska, "Określanie jakości oddawania barw źródeł światła parametrami przedstawionymi w zaleceniach IES TM-30-15 i CIE 013.3-1995", Przeglad Elektrotechniczny R. 93(6), 50 (2017). DirectLink J. Kowalska, I. Fryc, "Jakość oddawania barw współczesnych lamp fluorescencyjnych określona zdefiniowanym przez CIE wskaźnikiem wierności barwy oraz wskaźnikiem oddawania barw", Przeglad Elektrotechniczny R. 95(7), 94 (2019). DirectLink CIE 170-2:2015 DirectLink